2016
DOI: 10.5194/bg-13-6545-2016
|View full text |Cite
|
Sign up to set email alerts
|

Crop water stress maps for an entire growing season from visible and thermal UAV imagery

Abstract: Abstract. This study investigates whether a water deficit index (WDI) based on imagery from unmanned aerial vehicles (UAVs) can provide accurate crop water stress maps at different growth stages of barley and in differing weather situations. Data from both the early and late growing season are included to investigate whether the WDI has the unique potential to be applicable both when the land surface is partly composed of bare soil and when crops on the land surface are senescing. The WDI differs from the more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 43 publications
1
61
0
1
Order By: Relevance
“…Visible light VIs, such as the NGRDI, are often used to characterize vegetation if NIR information is lacking (Pérez et al 2000; Meyer and Neto 2008; Raymond et al 2005). Due to their low costs and low weight, consumer-grade true colour (RGB) digital cameras are particularly suitable for assessing green vegetation using UAS-based imaging systems (Torres-Sánchez et al 2014; Saberioon et al 2014; Hoffmann et al 2016a; Goodbody et al 2017; Jannoura et al 2015). Rasmussen et al (2016) evaluated the reliability of four VIs (ExG, NGRDI, NDVI, ENDVI) derived from consumer-grade RGB as well as CIR (colour-infrared) cameras mounted on UAS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible light VIs, such as the NGRDI, are often used to characterize vegetation if NIR information is lacking (Pérez et al 2000; Meyer and Neto 2008; Raymond et al 2005). Due to their low costs and low weight, consumer-grade true colour (RGB) digital cameras are particularly suitable for assessing green vegetation using UAS-based imaging systems (Torres-Sánchez et al 2014; Saberioon et al 2014; Hoffmann et al 2016a; Goodbody et al 2017; Jannoura et al 2015). Rasmussen et al (2016) evaluated the reliability of four VIs (ExG, NGRDI, NDVI, ENDVI) derived from consumer-grade RGB as well as CIR (colour-infrared) cameras mounted on UAS.…”
Section: Resultsmentioning
confidence: 99%
“…Even though CIR cameras are sometimes recommended rather than RGB cameras, they found no clear advantage of CIR images and concluded that RGB cameras are powerful tools for assessing green vegetation. Hoffmann et al (2016a) used the NGRDI based on UAS imagery to assess surface greenness of barley fields for the detection of crop water stress. In their study, they found a medium–strong correlation between the NGRDI and the NDVI and concluded that their results bode well for the use of the NGRDI as a greenness index.…”
Section: Resultsmentioning
confidence: 99%
“…The UAV instrumentation has previously been tested to derive drought stress in agricultural crops such as barley [54], olive [4,5], and fruit species [16]. UAV was also applied to study vegetation index linkages to water stress in grapevines [55] but not yet to investigate CWSI in a grapevine crop, as done in the present research and other studies [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be remembered that while correlated, our definition of vigour is fundamentally different from the definition of the NDVI detected by the GreenSeeker sensor. This difference may also be a contributing factor to its lower correlation with image-based vigour measurement by both MGP and UAV imaging systems [29].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, GRVI has been used to represent and proportionally quantify plant vigour. The index normalizes for variations in light intensities, has been a tested indicator of chlorophyll content in several crops and is shown to be positively correlated with traits such as biomass [28] and leaf area index [29], a quantity related to plant vigour. In this study, images of plant canopies are captured in the RGB channels, making an RGB-derived index suitable to represent vigour by both MGP and UAV.…”
Section: Introductionmentioning
confidence: 99%